On activities of anti-Bolshevik governments during the Civil War in Russia - E. A. Koshechkina (Омский научный вестник: Серия "Общество. История. Современность")
The need to re-evaluate the historical experience of the revolutionary events of 1917, the civil war and the subsequent establishment of the Bolshevik regime was and remains one of the topical issues of Russian history. The article is devoted to the functioning of the anti-Bolshevik government in the years of the civil war in Russia after 1917, and Covers the causes and background of the revolutionary events of February – October 1917, a possible alternative exit from the crisis of 1917. The reasons of defeat of «white movement», in particular, some aspects of agrarian policy of anti-Bolshevik governments and on a national question are considered